Cellular Restriction of Retrovirus Particle-Mediated mRNA Transfer - Galla, Melanie (American Society for Microbiology (ASM), 2008)
Analyzing cellular restriction mechanisms provides insight into viral replication strategies, identifies targets for antiviral drug design, and is crucial for the development of novel tools for experimental or therapeutic delivery of genetic information. We have previously shown that retroviral vector mutants that are unable to initiate reverse transcription mediate a transient expression of any sequence which replaces the gag-pol transcription unit, a process we call retrovirus particle-mediated mRNA transfer (RMT). Here, we further examined the mechanism of RMT by testing its sensitivity to cellular restriction factors and short hairpin RNAs (shRNAs). We found that both human TRIM5α and, to a lesser extent, Fv1 effectively restrict RMT if the RNA is delivered by a restriction-sensitive capsid. While TRIM5α restriction of RMT led to reduced levels of retroviral mRNA in target cells, restriction by Fv1 did not. Treatment with the proteasome inhibitor MG132 partially relieved TRIM5α-mediated restriction of RMT. Finally, cells expressing shRNAs specifically targeting the retroviral mRNA inhibited RMT particles, but not reverse-transcribing particles. Retroviral mRNA may thus serve as a translation template if not used as a template for reverse transcription. Our data imply that retroviral nucleic acids become accessible to host factors, including ribosomes, as a result of particle remodeling during cytoplasmic trafficking.